Pengaruh Citra Merek Dan Kualitas Produk Terhadap Keputusan Pembelian Smartphone Merek Vivo Pada Toko Bandung Jaya A.Y Patty Ambon - Yoel David Sampe; Marie Tahalele (P3M Politeknik Negeri Ambon, 2023)
This study aims to examine and analyze the influence of brand image and product quality on purchasing decisions for VIVO brand smartphones at the Bandung Jaya A. Y. Patty Ambon store. Data collection was carried out by distributing questionnaires to respondents and after that it was tested and analyzed using SPSS software version 21.0. According to the results of data processing, it can be concluded that the characteristics of respondents based on age are mostly 19 year old respondents with a percentage of 19%, while the characteristics of respondents based on work are mostly students with a percentage of 57%. Based on the test results of the coefficient of determination (R2) shows that 0.733 or about 73.3% of the purchasing decision variables can be influenced or explained by brand image and product quality variables, while the other 26.7% are influenced or explained by other variables not discussed in this study. Keywords: Brand Image and Product Quality